Comparison of Immunofluorescence Assays Results for Diagnosis of Rickettsial Diseases Using Direct Serum and Filter Paper Serum Spots - Sweety, Afroza Akbar; Munshi, Saif Ullah; Hossain, Mohammad Zaid; Islam, Baishakhi; Tabassum, Shahina; Ahmed, Imtiaz; Khan, Shahjalal; Khan, AHM Ejrarul Alam; Azad, Khan Abul Kalam (Journal of Dhaka Medical College, 2021)
Background: Rickettsial diseases are difficult to diagnose in Bangladesh due to low index of suspicion and lack of diagnostic facilities in most laboratories especially in rural areas. Immunofluorescence assay (IFA) is the gold standard serological test for diagnosis of Rickettsial diseases. For serological diagnosis of rickettsial diseases, use of filter paper is an inexpensive and convenient method for collecting, storing, and transporting of blood samples with little space without refrigeration. Current study shows that the rickettsial diseases were present in febrile patients in Bangladesh. The study also compared the results of direct serum by IFA and filter paper serum spot followed by IFA as an alternative way of testing frozen samples. Materials and Methods: This observational study for evaluation of rickettsial diseases from direct serum by IFA and sera dried on blotting paper followed by IFA at the department of Virology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. A total of 152 patients’ sera were selected by systemic random sampling of every 3rd sera of 556 febrile patients who were tested negative for dengue and or Chikungunya virus infection. Forty cases were confirmed by IFA from direct sera. In addition, 60 samples were selected from 152 sera by systemic random sampling of every 3rd sera for blotting on filter paper for further IFA test. Out of 60 sera, 35 were confirmed by IFA from direct sera and of the 35 confirmed positive cases, 31(88.6%) were positive by IFA after blotting paper assay. Taking the IFA of direct sera as gold standard test, the sensitivity, specificity, positive predictive value and negative predictive value of IFA from blotting paper eluted sera were 88%, 100%, 100% and 86% respectively. Conclusion: The study showed the use of filter paper is an inexpensive and convenient method for storing and transporting samples for serological tests like IFA in diagnosis of rickettsial diseases. J Dhaka Medical College, Vol. 28, No.2, October, 2019, Page 153-158